Classroom Record Keeping Made Simple : Tips for Time-Strapped Teachers. - Mierzwik, Nancy Diane (SAGE Publications, 2005)
This enlightening text provides tips, strategies, and best practices for finding additional daily time and creating enhanced documentation through better record-keeping management.